2007
DOI: 10.1080/13921657.2007.10512816
|View full text |Cite
|
Sign up to set email alerts
|

BREEDING PHENOLOGY AND SPATIO-TEMPORAL DYNAMICS OF POND USE BY THE YELLOW-BELLIED TOAD (BOMBINA VARIEGATA) POPULATION: THE IMPORTANCE OF POND AVAILABILITY AND DURATION

Abstract: Abstract. We analysed the spatial and temporal variation of breeding habitat availability and use by a yellow-bellied toad population in a mixed deciduous forest between 20032005. During this period, the number of temporary ponds was highly variable. Toads tended to exploit newly created breeding habitats or those of which hydroperiod increased due to precipitation. Ponds with intermediate and long duration were preferred for reproduction. We found no evidence of predator avoidance behaviour (aquatic invertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
22
2
1
Order By: Relevance
“…On the other hand, the results of the present study are in contrast with studies that describe B. variegata as a species preferring open pasture ponds [28][29]. Barandun and Reyer [28] found that B. variegata did not use cool or shaded as well as permanent ponds for spawning.…”
Section: Resultscontrasting
confidence: 56%
“…On the other hand, the results of the present study are in contrast with studies that describe B. variegata as a species preferring open pasture ponds [28][29]. Barandun and Reyer [28] found that B. variegata did not use cool or shaded as well as permanent ponds for spawning.…”
Section: Resultscontrasting
confidence: 56%
“…It shows plasticity in the number of breeding events and in the choice of spawning sites (Barandun & Reyer, 1997a;Guarino et al, 1998). It is usually associated with temporary water bodies that have limited canopy cover and high insolation, allowing high water temperatures and fast larval development, minimizing the threat of desiccation while decreasing predatory pressure on tadpoles (Hartel et al, 2007). Suggested explanations for the decline of the species focus on the loss of temporary wetlands, particularly those related to agricultural activities (Mirabile et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bombina variegata, R. temporaria and R. dalmatina are the most common species in temporary ponds, including the short duration ones. This is possible because the species have several adaptations to temporary pond-breeding, such as short larval periods; high phenotypic plasticity, and in the case of B. variegata, the multiple breeding during a season in synchronization with rainfall (Barandun & Reyer 1997a,b, 1998Loman 1999; for local studies see Hartel et al 2005Hartel et al , 2007b. Despite the considerable similarity in reproductive mechanisms the parental species of the Rana esculenta complex show a great degree of general morpho-anatomical and functional differentiation which results in a different susceptibility to environmental factors (Bucci et al 2000;Marracci & Ragghianti 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Intensive monitoring was carried out in two clusters of temporary ponds. For these two sites, the details regarding the temporal and spatial pond use by amphibians were already presented elsewhere (Hartel et al 2005(Hartel et al , 2007b.…”
Section: Surveysmentioning
confidence: 99%